Robotic Systems for Meteor Observing and Moon Impact Flashes Detection in Spain - José M. Madiedo; Josep M. Trigo-Rodríguez; José L. Ortiz; Nicolás Morales (Advances in Astronomy)
A robotic observatory has been setup in the south-west of Spain with the aim to study meteoroids interacting with the Earth's atmosphere and meteoroids impacting on the Moon's surface. This is achieved by using an array of high-sensitivity CCD video cameras and three automated Schmidt-Cassegrain telescopes. We summarize here the main characteristics of this new facility.